Arnold Röhring and the residential garden in siary in view of the garden art trends of that time - Zachariasz, Agata (Видавництво Львівської політехніки, 2016)
The article discusses the garden in Siary near Gorlice located in the territory of the former Galicia. The palace complex owned by the senator Wladyslaw Dlugosz was famous for its sophisticated style, a magnificent use of genius loci, a perfect setting in landscape, and scenic connections. The garden combined features typical of eclecticism and naturalism. According to the family sources, it was designed by Arnold Röhring, the designer of Stryiskyi Park in Lviv. The work also attempts to determine similarities in terms of features typical of the works designed by Röhring and the garden in Siary in view of landscape architecture trends of that time. У статті представлено сад при палаці в Сярах, розташований неподалік від Горлиць у колишній Галичині. Палацовий комплекс належав сенаторові Владиславу Длугошу і був відомий своїм витонченим стилем, прекрасним використанням genius loci, досконалого розташування у ландшафті та візуальних зв’язках. Сад поєднував характерні риси еклектики та натуралізму. За родинними переказами, автором проекту парку був Арнольд Рерінг – автор проекту Стрийського парку у Львові. У статті представлено також спробу пошуку аналогічних елементів характерних для творчості Рерінга та саду при палаці в Сярах з тогочасними тенденціями у ландшафтному мистецтві.
Арнольд Рерінг та сад при палаці в сярах нафоні сучасних тенденцій у ландшафтному мистецтві
Keywords: garden styles; naturalism; eclecticism; picturesque; garden composition; parterres and bedstypes; ландшафтні стилі; натуралізм; еклектизм; мальовничість; композиція саду; типи партерів рабаток